Tools and Algorithms for the Construction and Analysis of Systems 16th International Conference, TACAS 2010, Held as Part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2010, Paphos, Cyprus, March 20-28, 2010. Proceedings - Esparza, Javier; Majumdar, Rupak; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 16th International Conference on Tools and Algorithms for the Construction and Analysis of Systems, TACAS 2010, held in Paphos, Cyprus, in March 2010, as part of ETAPS 2010, the European Joint Conferences on Theory and Practice of Software. The 35 papers presented were carefully reviewed and selected from 134 submissions. The topics covered are probabilistic systems and optimization, decision procedures, tools, automata theory, liveness, software verification, real time and information flow, and testing.
Invited Talks -- Embedded Systems Design Scientific Challenges and Work Directions -- Antichain Algorithms for Finite Automata -- Probabilistic Systems and Optimization -- Assume-Guarantee Verification for Probabilistic Systems -- Simple O(m logn) Time Markov Chain Lumping -- Model Checking Interactive Markov Chains -- Approximating the Pareto Front of Multi-criteria Optimization Problems -- Decision Procedures -- An Alternative to SAT-Based Approaches for Bit-Vectors -- Satisfiability Modulo the Theory of Costs: Foundations and Applications -- Optimal Tableau Algorithms for Coalgebraic Logics -- Blocked Clause Elimination -- Tools I -- Boom: Taking Boolean Program Model Checking One Step Further -- The OpenSMT Solver -- Stranger: An Automata-Based String Analysis Tool for PHP -- Automata Theory -- When Simulation Meets Antichains -- On Weak Modal Compatibility, Refinement, and the MIO Workbench -- Rational Synthesis -- Efficient Büchi Universality Checking -- Liveness -- Automated Termination Analysis for Programs with Second-Order Recursion -- Ranking Function Synthesis for Bit-Vector Relations -- Fairness for Dynamic Control -- Tools II -- JTorX: A Tool for On-Line Model-Driven Test Derivation and Execution -- SLAB: A Certifying Model Checker for Infinite-State Concurrent Systems -- Tracking Heaps That Hop with Heap-Hop -- Software Verification -- Automatic Analysis of Scratch-Pad Memory Code for Heterogeneous Multicore Processors -- Simplifying Linearizability Proofs with Reduction and Abstraction -- A Polymorphic Intermediate Verification Language: Design and Logical Encoding -- Trace-Based Symbolic Analysis for Atomicity Violations -- Tools III -- ACS: Automatic Converter Synthesis for SoC Bus Protocols -- AlPiNA: An Algebraic Petri Net Analyzer -- PASS: Abstraction Refinement for Infinite Probabilistic Models -- Real Time and Information Flow -- Arrival Curves for Real-Time Calculus: The Causality Problem and Its Solutions -- Computing the Leakage of Information-Hiding Systems -- Statistical Measurement of Information Leakage -- SAT Based Bounded Model Checking with Partial Order Semantics for Timed Automata -- Testing -- Preemption Sealing for Efficient Concurrency Testing -- Code Mutation in Verification and Automatic Code Correction -- Efficient Detection of Errors in Java Components Using Random Environment and Restarts.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer Science; Software Engineering; Logics and Meanings of Programs; Computer Communication Networks; Programming Languages, Compilers, Interpreters; Artificial Intelligence (incl. Robotics).; Programming Techniques